2007
DOI: 10.1002/ett.1238
|View full text |Cite
|
Sign up to set email alerts
|

IB‐DFE receivers with space diversity for CP‐assisted DS‐CDMA and MC‐CDMA systems

Abstract: SUMMARYMulti-Carrier Code Division Multiple Access (MC-CDMA), currently regarded as a promising multiple access scheme for broadband communications, is known to combine the advantages of an Orthogonal Frequency Division Multiplexing (OFDM)-based, Cyclic Prefix (CP)-assisted block transmission with those of CDMA systems. Recently, it was recognised that DS-CDMA (Direct Sequence) implementations can also take advantage of the benefits of the CP-assisted block transmission approach, therefore enabling an efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…These performance are usually obtained by means of lengthy Monte Carlo simulations and it would be desirable to analytically obtain the BER performance of IB-DFE receivers. Since the overall noise plus residual Inter-Symbol Interference (ISI) is approximately Gaussian at the FDE output, it can be obtained an estimate of the BER from the MSE at the FDE output for each iteration [8]. These BER estimates are very accurate for the linear FDE, however, they present a non-negligible error in the iterative FDE case and in this paper it is shown that the error is a function of the number of multipath propagation components, as well as the MSE.…”
Section: Introductionmentioning
confidence: 99%
“…These performance are usually obtained by means of lengthy Monte Carlo simulations and it would be desirable to analytically obtain the BER performance of IB-DFE receivers. Since the overall noise plus residual Inter-Symbol Interference (ISI) is approximately Gaussian at the FDE output, it can be obtained an estimate of the BER from the MSE at the FDE output for each iteration [8]. These BER estimates are very accurate for the linear FDE, however, they present a non-negligible error in the iterative FDE case and in this paper it is shown that the error is a function of the number of multipath propagation components, as well as the MSE.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, there has been significant interest in the design of nonlinear FDE in general and decision feedback FDE in particular, with the IB-DFE being the most promising nonlinear FDE [7,8]. IB-DFE was originally proposed in [9] and was extended for a wide range of scenarios in the last 10 years, ranging from diversity scenarios [10,11], MIMO systems [12], CDMA systems [13,14], and multi-access scenarios [15,16], among many other. Essentially, the IB-DFE can be regarded as a low complexity turbo equalizer [17][18][19][20] implemented in the frequency domain that do not require the channel decoder output in the feedback loop, although true turbo equalizers based on the IB-DFE concept can also be designed [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, the residual ICI after MMSE-FDE limits the achievable BER performance improvement. In order to further reduce the residual ICI after MMSE-FDE, iterative MMSE-FDE and ICI cancellation (ICIC) was proposed [4,5]. In this scheme, at first, a series of one-tap Rx FDE and despreading is carried out.…”
Section: Introductionmentioning
confidence: 99%